Assessing the knowledge, attitude and perception of Extended Reality (XR) technology in Pakistan’s Healthcare community in an era of Artificial Intelligence - Khan, Zoha; Adil, Talha; Oduoye, Malik Olatunde; Khan, Bareerah Shaukat; Ayyazuddin, Meher (Frontiers in Medicine, 2024)
Background and Objectives: The Extended Reality (XR) technology was established by combining elements of Virtual Reality and Augmented Reality, offering users the advantage of working in a virtual environment. The study aimed to evaluate medical professionals' and students' knowledge, attitudes, and practices regarding using XR technology in Pakistan's healthcare system and identify its benefits, drawbacks, and implications for the system's future. Methodology: A cross-sectional study was executed by circulating a self-structured online questionnaire among the Medical Community across Major Cities of Pakistan using various social media platforms as available sampling. The sample size was calculated to be 385 using RAOSOFT. Cronbach's alpha was calculated as 0.74. The Exploratory Factor Analysis (EFA) conducted on the dataset was validated using the Kaiser-Meyer-Olkin (KMO) measure and Bartlett's Test of Sphericity. The KMO value of 0.752 indicates adequate sampling, and Bartlett's Test was significant (χ² (435) = 2809.772, p < 0.001), confirming the suitability of the data for factor analysis. Statistical analysis was done using SPSS-25, and data description was done as frequency and percentage. Pearson correlation and regression analysis kept p value<0.05% significant. Results: Approximately 54.8% of 406 participants conveyed their familiarity with XR technologies. The majority of participants (83.8%) believed that using XR technology effectively enhanced medical education and patient care in Pakistan. Regarding clinical outcomes, 70.8% believed XR improved the efficiency of procedures and 52.8% agreed XR would lead to more device-dependent systems and eradicating human error (32.4%). Major barriers to XR integration included ethical and privacy issues (63.9%), lack of technological advancements in Pakistan (70%), and lack of ample knowledge and training of XR among health care professionals (45.8%). A correlation between the mean Attitude (MA) score and the mean Perception (MP) score was found to be moderately positive and significant (r = .356, p < .001). Hence, the hypothesis 3 was supported. Conclusion: XR technology has the potential to enhance medical education and patient care in Pakistan, but its adoption faces significant challenges, including ethical concerns, technological gaps, and inadequate training. The study's findings highlight the need to address these issues to maximize the benefits of XR in healthcare.